Pengaruh Motivasi, Mutasi dan Kualitas Pelayanan Publik terhadap Kinerja Pegawai Melalui Kepuasan Kerja sebagai Variabel Intervening (Literature Review Manajemen Sumber Daya Manusia) - Henderika Medah, Mardiana; E. H. J. FoEh, John; A. Manafe, Henny (Dinasti Review Publisher, 2023)
This scientific work intends to find out motivation (X1), mutation (X2), and quality of public services (X3) in influencing performance (Y) through job satisfaction (Z) which are intervening variables. Motivation is very influential for those who give motivation and those who receive it. Employee mutations also affect performance because placing the right people according to their educational background can make a major contribution to the organization. The quality of public services provided is also able to provide satisfaction to the community so that the resulting performance also has a positive impact. Customers who are impressed with the quality of public services provided will make these customers come again and promote to others so that the company can get big profits. Maximum performance is obtained from human resources who have passion and work experience. The maximum performance brings satisfaction to employees in a company or organization.